Protective Effect of an Exopolysaccharide Produced by Lactiplantibacillus plantarum BGAN8 Against Cadmium-Induced Toxicity in Caco-2 Cells - Brdarić, Emilija; Soković Bajić, Svetlana; Đokić, Jelena; Đurđić, Slađana; Ruas-Madiedo, Patricia; Stevanović, Magdalena; Tolinački, Maja; Dinić, Miroslav; Mutić, Jelena; Golić, Nataša; Živković, Milica (Frontiers in Microbiology, 2021)
Cadmium (Cd) ranks seventh on the list of most significant potential threats to human health based on its suspected toxicity and the possibility of exposure to it. It has been reported that some bacterial exopolysaccharides (EPSs) have the ability to bind heavy metal ions. We therefore investigated the capacity of eight EPS-producing lactobacilli to adsorb Cd in the present study, and Lactiplantibacillus plantarum BGAN8 was chosen as the best candidate. In addition, we demonstrate that an EPS derived from BGAN8 (EPS-AN8) exhibits a high Cd-binding capacity and prevents Cd-mediated toxicity in intestinal epithelial Caco-2 cells. Simultaneous use of EPS-AN8 with Cd treatment prevents inflammation, disruption of tight- junction proteins, and oxidative stress. Our results indicate that the EPS in question has a strong potential to be used as a postbiotic in combatting the adverse effects of Cd. Moreover, we show that higher concentrations of EPS-AN8 can alleviate Cd-induced cell damage.